Scanning Tunnel Microscopy of Coatings with Titan Carbonitride Nanoparticles and Their Properties; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Kuznetsov P. V. Pavel Viktorovich; Galchenko N. K. Nina; Rakhmatulina T. V. Tanzilya; Samartsev V. P. Victor; Kolesnikova K. A. Ksenia; Laptev R. S. Roman Sergeevich; Babikhina (Babihina) M. N. Mariya Nikolaevna (2017, 2017)
Title screen